Global burden of diarrhea disease in the older adult and its attributable risk factors from 1990 to 2021: a comprehensive analysis from the global burden of disease study 2021 - Zhao, Wen-Zhuo; Wang, Jing-Yi; Zhang, Min-Na; Wu, Shang-Nong; Dai, Wei-Jie; Yang, Xiao-Zhong; Wang, Hong-Gang (Frontiers in Public Health, 2025)
IntroductionDiarrhea disease among the older adult is an underappreciated global health issue despite its substantial burden. This study provides a comprehensive analysis of the epidemiological trends of diarrhea in individuals over 65 years, examining incidence, prevalence, mortality, and disability-adjusted life-years (DALYs) from 1990 to 2021.MethodsUtilizing data from the Global Burden of Diseases (GBD) 2021, this cross-sectional study assesses the older adult population across 204 countries and territories. The analysis includes metrics such as incidence, prevalence, mortality, DALYs, and estimated annual percentage changes (EAPCs), stratified by region, country, age, sex, and Sociodemographic Index (SDI).ResultsA nearly 200% increase in incidence and prevalence was observed worldwide, with the highest rise in those over 95 years. Mortality and DALYs have declined, especially in the 65–69 age group. High SDI regions showed the largest increase in incidence rates and are the only areas with increasing mortality and DALYs trends. Unsafe water sources emerged as the primary risk factor for diarrhea-related deaths among the older adult.DiscussionThe burden of diarrhea in the older adult has significantly increased, particularly in high-income regions, warranting targeted interventions. The positive correlation between EAPC and the Human Development Index underscores the need for improved water safety to mitigate the disease burden. This study's findings are crucial for shaping public health strategies and informing policy decisions regarding the older adult population.